Cultivating a Culture of Safety in the Hospitality Industry : The Interplay of Employee Training, Awareness, and Sexual Harassment Mitigation - Prasetya, Farid Adi; Veno, Andri; Ariani, Kurnia Rina (Universitas Muhammadiyah Surakarta, 2024)
This research explores the complex dynamics of sexual harassment in the hospitality industry, specifically in five provinces in Indonesia known for their high concentration of hotels. It also examines a selection of star-rated hotels that have implemented training programs to address sexual harassment. This study delves into the relationship between employee training, awareness, and sexual harassment prevention. It adopts a quantitative approach with the participation of 140 HR managers from star-rated hotels. The results highlight a strong connection between staff training and increased sexual harassment mitigation, underscoring the importance of thorough training programs. Employee awareness plays a vital role in influencing the effectiveness of preventative measures. Practical implications involve industry-wide efforts to promote a safety culture and enforce zero-tolerance policies via specialized training and public awareness campaigns. Although the study is focused on specific regions and establishments, it lays the groundwork for further exploration into sexual harassment in various hospitality settings, training techniques, cross-cultural factors, and changing regulations. Future research needs to delve deeper into the complexities of sexual harassment within the broad industry.